Implementasi Strategi Conventional Marketing Guna Meningkatkan Penjualan Pada Usaha Bancreps - Yea Aprilia Silvana; Ira Nuriya Santi; Syamsul Bahri Dg. Parani; Juliana Kadang (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
In today's modern era, marketing is often referred to as the main influence of a business that produces goods or services. Marketing requires a variety of continuous development and strategy changes in order to maximize the potential for success and achieve sustainability. Regarding marketing strategy, if it is not able to control the existing growth, it will not only result in the downfall of the business but also the loss of customers and a decrease in the amount of revenue. The methodology used in this research is a qualitative descriptive method that aims to conduct a thorough investigation of conventional marketing WOM strategies. In this modern era, Bancreps chose a conventional marketing strategy for its business. Marketing carried out by Bancreps can be done more in-depth by using SWOT analysis theory. However, Bancerps to use digital platforms to reach a wider range of customers than just relying on traditional marketing strategies.